161 Feasibility of cardiovascular magnetic resonance surveillance of LV function in women with breast cancer treated with trastuzumab. (6th June 2022) - bevis, lydia; Siddiqui, Zuhayr; Farley, Jonathan; Cheng, Vinton; Artis, Nigel; Kilcullen, Niamh; Exley, Claire; Oswal, Dilip; Swoboda, Peter
Abstract : Background: Cardiovascular magnetic resonance (CMR) is established as the gold standard test for assessment of cardiac function due to high interstudy reproducibility. Patients with HER2-postive breast cancer are typically treated with trastuzumab ± anthracycline chemotherapy during which guidelines recommend serial monitoring of LV function. CMR is not routinely used because of availability and cost. We aimed to evaluate the rate of chemotherapy induced cardiotoxicity in patients monitored by CMR. Methods: We retrospectively recruited 85 women who had started trastuzumab chemotherapy between February 2018 and October 2020. All patients underwent at least two CMR surveillance scans of a protocol including cine imaging in long axis and a short axis stack (10 mm slice thickness, no gap). Clinical data including baseline risk factors were assessed and patients were followed up for events and clinical decision to start heart failure therapy (ACE inhibitors or betablockers). We defined chemotherapy induced cardiotoxicity as the clinical decision to start heart failure therapy or a drop in left ventricular ejection fraction (LVEF) ≥10% to <55% (1). Results: Patients had an average of 4 (±1.1) scans. Of the 85 patients, 20 (24%) fulfilled our definition of chemotherapy induced cardiotoxicity including 16 (19%) who were started on heart failure treatment and 4 (5%) with a drop in LVEF ≥10% to <55%. Only 3 (4%) patients had their trastuzumab therapy ceased due to a drop of >10% in LVEF. However, none of these patients were commenced on heart failure medications. No patients were admitted to hospital with symptoms of heart failure. Patients with chemotherapy induced cardiotoxicity had numerically higher prevalence of hypertension, diabetes and hypercholesterolaemia but none of these reached statistical significance. There was no difference in baseline LVEF, LV end-diastolic volume or end-systolic volume (table 1). Conclusion: CMR screening of patients undergoing trastuzumab chemotherapy is feasible. The incidence of chemotherapy induced cardiotoxicity in our cohort was 24% which is comparable to the 13–27% previously reported (2). Further prospective studies are needed to establish if additional CMR biomarkers can improve detection of chemotherapy induced cardiotoxicity and alter outcomes. References: 1. Tan L-L, Lyon AR. Heart 2021;107 :1254–1266 2. Slamon DJ, Leyland-Jones B, Shak S, et al. N Engl J Med 2001 Mar 15;344 (11):783–92. Conflict of Interest: Nil